"For the World's Complexity": Intellectual "Condensing of Reality" in O. Mandelstam's Works. Issue 2 (4th March 2021) - Kondakov, Igor V.; Brusilovskaya, Liliya B.
ABSTRACT: This article focuses on the theoretical foundations of Osip Mandelstam's semantic poetics, its cultural–philosophical richness, and its aesthetic novelty. The principal features of Mandelstam's poetic world are its metaphorical and associative complexity and persistent struggle with metaphysical "emptiness." Guided by Yu. Tynianov's law that verse structure should be tight and unified, the poet achieves an exceptional "condensing" of his poetic texts, using this for his particular creative strategies aimed at enhancing the polysemy of the word, expanding its cultural–historical context, achieving semantic uncertainty, and combining philosophical "connectedness" with associative "disconnectedness." These strategies include a reliance on semantic clusters, which involve "bunches" of contradictory meanings, chains of binary and ternary deep structures of text, and a dramatic combination of binarity and ternarity. Mandelstam's creation of a "moiré" texture in his poetic texts contributes to the deepening of their tragic outlook of confusion and hopelessness, which corresponds to the realities of the Stalin era and the impending Great Terror.